The application of the Generalized Lord’s Chi-Square method in identifying biased items - Herwin, Herwin; Phonn, Sophak (Graduate School, Universitas Negeri Yogyakarta, 2019)
This study aims to find out the results of the analysis of item bias by using Generalized Lord's Chi-square test method on the test instrument of elementary school examination in a sub-district of Gowa Regency, Indonesia. This research is explorative research using quantitative approach. This research was conducted in the second semester of the academic year of 2017/2018 at the Bontomarannu District Elementary School in Gowa Regency. Data collection technique used is documentation. The data in this study were analyzed using the DIF method of Generalized Lord Chi-Square test. The results show that in using the Generalized Lord Chi-square method, from 20 items of mathematics test of school exam in Bontomarannu District Elementary School in Gowa Regency of the academic year 2017/2018, there are two items which are detected containing the bias (DIF), i.e., item 5 and item 11, while the rest are not.